Proceedings of the 22nd ACM International Conference on Multimedia 2014
DOI: 10.1145/2647868.2655038
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Thousands of Legal Entities through Instance-based Visual Classification

Abstract: International audienceThis paper considers the problem of recognizing legal en-tities in visual contents in a similar way to named-entity recognizers for text documents. Whereas previous works were restricted to the recognition of a few tens of logotypes, we generalize the problem to the recognition of thousands of legal persons, each being modeled by a rich corporate identity automatically built from web images. We intro-duce a new geometrically-consistent instance-based classifi-cation method that is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The only achievement dealing with more realistic numbers of entities and richer visual identities is the recent work of Leveau et al [7]. The authors actually reported in that paper an experiment with more than 5,000 entities represented by a (noisy) training set of 370K images automatically crawled through a web search engine.…”
Section: Introductionmentioning
confidence: 99%
“…The only achievement dealing with more realistic numbers of entities and richer visual identities is the recent work of Leveau et al [7]. The authors actually reported in that paper an experiment with more than 5,000 entities represented by a (noisy) training set of 370K images automatically crawled through a web search engine.…”
Section: Introductionmentioning
confidence: 99%